PENGARUH PENGGUNAAN GADGET TERHADAP KEMANDIRIAN BELAJAR MAHASISWA PENDIKAN MATEMATIKA UNIVERSITAS MUSAMUS - Andi Sitti Suhartini; Etriana Meirista; Khumaeroh Dwi Nur'aini (Musamus Journal of Mathematics Education, 2018)
This study aims to determine the significance of the influence of gadget usage on student independence learning in Mathematics Education Department of Musamus University. This research is quatitative research. The population in this study was students of Mathematics Education of Musamus University amounted to 210 students. Sampling technique used is convenience non probability sampling technique and obtained 78 students as sample. Data collection techniques used were questionnaire and interview, then the data from the questionnaire were analyzed using simple correlation and linear regression analysis. The result of the research shows that there is influence of gadgets usage on the independence learning of students in Mathematics Education of Musamus University, in which there is a relationship between the "medium" category between gadgets usage and the independence learning of students in Mathematics Education of Musamus University. Contribution given by gadget usage variable to the independence of learning as 27.2%.